Effect of delayed diagnosis on neuroendocrine function in individuals with suprasellar germ cell tumors - Tong, Tao; Xu, Jian; Chen, Han; Mo, Caiyan; Liang, Dan; Zhong, Liyong (Frontiers in Endocrinology, 2024)
The impact of delayed diagnosis on tumor-related prognosis appears to be minimal in individuals with intracranial germ cell tumors (iGCTs). However, its effect on neuroendocrine functions remains unclear. We aimed to assess the effects of delayed diagnosis on neuroendocrine function in individuals with suprasellar GCTs.We conducted a retrospective cohort study of 459 individuals with suprasellar GCTs and categorized them into two groups based on disease duration: delayed diagnosis (> 6 months) and non-delayed diagnosis (≤ 6 months). We compared endocrinological symptoms, neuroendocrine dysfunction and its grading (categorized into 0-3 grades based on severity), and recovery from neuroendocrine dysfunction in both groups.Results: Patients with delayed diagnosis exhibited higher incidences of amenorrhea, slow growth, fatigue, and polyuria/polydipsia. Neuroendocrine dysfunction, including central adrenal insufficiency (CAI), central hypothyroidism (CHT), arginine vasopressin deficiency (AVP-D), growth hormone deficiency, hypogonadism, and hyperprolactinemia, was more pronounced in the delayed diagnosis group at diagnosis, the end of treatment, and the last follow-up. Furthermore, individuals with delayed diagnosis showed higher grades of neuroendocrine dysfunction at diagnosis (OR=3.005, 95% CI 1.929-4.845, p<0.001), end of oncologic treatment (OR=4.802, 95% CI 2.878-8.004, p<0.001), and last follow-up(OR=2.335, 95% CI 1.307-4.170, p=0.005) after adjusting for confounders. Finally, less recovery, particularly in CAI, CHT, and AVP-D, was seen among the group with delayed diagnosis after treatment.Among individuals with suprasellar GCTs, delayed diagnosis is associated with increased, more severe, and less recovered neuroendocrine dysfunction, emphasizing the importance of early diagnosis and treatment to reduce neuroendocrine dysfunction.